Challenges and Opportunities in Implementing Green Data Centers in Indonesia Toward Sustainable Digital Infrastructure - Liza Mahavianti Syamsuri; Whildan Pakartipangi (Jurnal Penelitian Pendidikan IPA, 2025)
This article aims to explore the challenges and opportunities of implementing green data centres in Indonesia, focusing on regulatory influences, technological advancements, financial implications, and competitive advantages. Primary research was conducted through interviews with key stakeholders, including data centre providers, regulatory experts, energy suppliers, members of the data centre association, representatives from training institutions, and climate and energy economists. Secondary research drew from academic papers, published articles, and industry reports to supplement the findings. The study identified significant challenges in transitioning to green data centres in Indonesia. Key issues include the state electricity company PLN’s reliance on coal for electricity and the limited availability of renewable energy power plants, despite the country’s abundant renewable energy resources. Financial obstacles were noted, such as high initial capital expenditures (Capex) for advanced cooling systems and generators, and high operational expenditures (Opex) for electricity and fuel. However, the adoption of green technologies can reduce long-term Opex by improving energy efficiency. Regulatory gaps and the absence of targeted incentives further complicate the transition to green data centres. Adherence to international standards can provide a framework for sustainable practices, but there remains a significant talent gap in the data centre industry. Strategies to overcome these challenges include adopting renewable energy through Renewable Energy Certificates (RECs), implementing advanced cooling technologies, and utilizing energy-efficient servers and Data Center Infrastructure Management (DCIM) tools. Collaborating with suppliers who meet green criteria is also critical. Transitioning to green data centres offers a competitive edge by attracting clients with green targets and reducing emissions. However, higher initial costs may deter providers, making long-term financial planning essential. This study provides valuable insights for governments and industry stakeholders, emphasizing the importance of sustainable data centre development as part of Indonesia’s journey toward a greener economy.